2018
DOI: 10.1111/joim.12849
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbidity on disease characteristics, treatment intent and outcome in diffuse large B‐cell lymphoma: a Swedish lymphoma register study

Abstract: W€ asterlid T, Mohammadi M, Smedby KE,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 51 publications
5
34
0
Order By: Relevance
“…In contrast, comorbidity was associated with a lower relapse risk before death as comorbid patients were more likely to die of other causes. These findings are consistent with recent Swedish registry data analysing CCI as a comorbidity index [9]. Together, our data suggest that increasing age and comorbidity impacts nonlymphoma-specific mortality but not lymphoma-specific mortality.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, comorbidity was associated with a lower relapse risk before death as comorbid patients were more likely to die of other causes. These findings are consistent with recent Swedish registry data analysing CCI as a comorbidity index [9]. Together, our data suggest that increasing age and comorbidity impacts nonlymphoma-specific mortality but not lymphoma-specific mortality.…”
Section: Discussionsupporting
confidence: 93%
“…However, there are only limited data outside of clinical trials assessing the effect of gender on outcomes in older patients when using the standard 375 mg/m 2 21‐day schedule. A large registry study demonstrated that male gender is associated with inferior survival by univariable analysis across all ages receiving various ‘curative' regimens [all‐cause death HR 0·81 (95% CI 0·71–0·92); lymphoma‐specific death HR 0·82 (95% CI 0·70–0·97)] (Wästerlid et al , ) but no studies exist specifically in non‐trial elderly patients, particularly those aged ≥80 years, to assess the prognostic relevance of gender in R‐CHOP‐treated patients for whom detailed dose intensity information is also known.…”
Section: Baseline Clinical Characteristics Of Elderly Dlbcl Accordingmentioning
confidence: 99%
“…The negative prognostic impact of comorbidities is well established for non-Hodgkin lymphoma patients overall (Wieringa et al, 2014;Saygin et al, 2017;Antic et al, 2018;Wasterlid et al, 2018). For example, in a study of 962 diffuse large B-cell lymphoma (DLBCL) patients, a high comorbidity score was independently associated with a threefold increased risk of death (Antic et al, 2018), and among elderly patients comorbidity had a better discriminative power than the International Prognostic Index (IPI).…”
Section: Introductionmentioning
confidence: 99%